The Value of Community Capitals in Sustainable Urban Development: A Qualitative Exploration of Urban Informal Workers - Ivy Chumo; Blessing Mberu; Caroline Kabaria (Challenges)
Urban informality, often viewed negatively, is not solely the product of the urban poor but also reflects the failure of formal systems to adapt. Informal workers, who make up about 61% of the global workforce, operate outside formal labor laws and significantly contribute to urban development. Understanding and harnessing community capitals are vital for sustainable urban development. This qualitative study explored the community capitals framework (CCF) in an urban context, addressing the limitations of quantitative data on CCF, which often overlooks critical social factors. This study team conducted in-depth interviews with 36 informal service providers from the education, healthcare, water, sanitation, and solid waste management sectors. Additionally, four local leaders from two urban informal settlements in Nairobi, Kenya, were interviewed. The data from the transcripts were analyzed using thematic framework analysis, guided by the community capitals framework. We identified seven forms of community capital that benefit informal workers: natural, cultural, human, social, political, financial, and built. Human capital, which focuses on skills and qualities, was the most frequently utilized, followed by social capital, which centers on connections and relationships. Next in importance were financial and political capital. Although cultural capital was the least implemented, it was described as important for reflecting community knowledge and traditions. Examples of these capitals in action included solid waste workers, manual pit emptiers, education providers, health workers, and water service providers, who all contributed to urban development and well-being through waste management, sanitation, education, healthcare, and access to clean water. In conclusion, service providers use community capitals as a planning tool to understand dynamics, refine strategies, and build trust for urban development. Each capital functions like a community bank account, containing strengths and opportunities. Although cultural capital was ranked last, it warrants further research to explore its drivers. Additional research is needed to fully grasp the relationships among the various capitals and their impact on service delivery.